Comparative analysis of philosophy, organizational structure and development assistance mechanism of major multilateral development banks - Hossain, Shah Sujat (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Masters of Business Administration, 2017.